Measurement and analysis system for bicycle field test studies - Koellner, A.; Cameron, C. J.; Battley, M. A. (Procedia Engineering, 2014)
The work presented describes the development of a measurement and analysis system for bicycle field test studies capable of measuring structural responses including strain and acceleration. The system incorporates 24 sensors measuring strain, 4 sensors measuring acceleration, a stand-alone data acquisition unit weighing 1.7 kg which can be mounted behind the seat post and an offline programme analysing the data obtained. The system has been fully implemented on a BMX bicycle for the work presented herein. Piezo-electric accelerometers and resistance strain gauges are used as sensors which are wired to the data acquisition (DAQ) unit. The DAQ unit consists of a controller-chassis, 4 signal conditioning modules and specific application software. The software which controls the measurement process performs sensor calibration, simultaneous 24 bit data acquisition with a sampling frequency of 1000 Hz, signal conditioning and data storage. The sampling frequency was established as optimal in specifically designed assessment tests. The data is post-processed to determine the frequency responses, maximum accelerations and strains and to illustrate the time behaviour of accelerations and strains. The measurement and analysis system is validated in common cycling scenarios and a race simulation on a race track. The system is applicable to different types of bicycles and enables comprehensive investigations of structural phenomena.